Electronically tunable active filters with operational transconductance amplifiers - Malvar, Henrique S.; Malvar, Henrique S. (IEEE Transactions on Circuits and Systems, 1982)
The design of voltage- or current-controlled active filters with operational transconductance amplifiers (OTA’s) is much less expensive than with analog multipliers. This paper presents some experimental results on known circuits and a new configuration which allows the electronic control of the absolute bandwidth of a biquad.